2021
DOI: 10.1016/j.ecolecon.2020.106821
|View full text |Cite
|
Sign up to set email alerts
|

Restoring cultivated agrobiodiversity: The political ecology of knowledge networks between local peasant seed groups in France

Abstract: This article, using an institutional and political ecological perspective, analyses the role of knowledge networks supporting peasant seed groups in France. These groups promote a dynamic approach to agrobiodiversity restoration, developing new models of collaborative "peer-to-peer genetics" and distributed participatory breeding. Our analysis focuses here on the small grain cereal participatory breeding group. Based on detailed qualitative surveys and a network formalization, our study provides a better under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…About KE, Bowonder and Miyake (2000) analyzed technological innovation issues by combining the theories of knowledge management and the concepts of ecosystem. On this basis, some scholars also found that building a knowledge ecosystem of organizations can improve the technological innovation (Eikhof et al , 2019; Mazé et al , 2021; Turaeva and Hornidge, 2013). For instance, based on organizational ecology, Becker (2007) proposed the functions of the workplace in creating opportunities and barriers, and these functions can affect the flow and development of all kinds of resources including information, knowledge and so on.…”
Section: Literature Reviewmentioning
confidence: 98%
“…About KE, Bowonder and Miyake (2000) analyzed technological innovation issues by combining the theories of knowledge management and the concepts of ecosystem. On this basis, some scholars also found that building a knowledge ecosystem of organizations can improve the technological innovation (Eikhof et al , 2019; Mazé et al , 2021; Turaeva and Hornidge, 2013). For instance, based on organizational ecology, Becker (2007) proposed the functions of the workplace in creating opportunities and barriers, and these functions can affect the flow and development of all kinds of resources including information, knowledge and so on.…”
Section: Literature Reviewmentioning
confidence: 98%
“…However, taxonomic expertise is only one means of action among others, because ecosystems are sometimes destroyed after being inventoried and studied. At the same time, hybrid collectives (not composed solely of experts) promote participatory research and management that sometimes prove to be very useful for the consideration and preservation of plant environments [76].…”
Section: Wild and Ornamental Plants: Recommendations And Concrete Measuresmentioning
confidence: 99%
“…Despite its potential, so far, the adoption of SI practices is relatively low, as only 9% of global agricultural land is estimate to operate under some form of SI (Pretty et al, 2018), and especially low in countries generally characterised by industrialised agricultural systems. Despite their benefits, implementing such practices often implies (initial) increased costs for farmers (Rosa-Schleich et al, 2019), who struggle to reduce agrochemical use (Bakker et al, 2021;Chèze et al, 2020;Mann, 2018), diversify their crop rotations (Jouan et al, 2020;Lemken et al, 2017), or improve on-farm biodiversity (Kirchweger et al, 2020;Mazé et al, 2021;Plaas et al, 2019). Additionally, a change in practices often requires the reorganisation of relations with downstream partners at value chain level, for example in the case of crop diversification and mixed cropping (Meynard et al, 2017).…”
Section: Introductionmentioning
confidence: 99%